Dual soluble epoxide hydrolase inhibitor – farnesoid X receptor agonist interventional treatment attenuates renal inflammation and fibrosis - Khan, Md. Abdul Hye; Nolan, Benjamin; Stavniichuk, Anna; Merk, Daniel; Imig, John D. (Frontiers in Immunology, 2024)
Introduction Renal fibrosis associated with inflammation is a critical pathophysiological event in chronic kidney disease (CKD). We have developed DM509 which acts concurrently as a farnesoid X receptor agonist and a soluble epoxide hydrolase inhibitor and investigated DM509 efficacy as an interventional treatment using the unilateral ureteral obstruction (UUO) mouse model. Methods Male mice went through either UUO or sham surgery. Interventional DM509 treatment (10mg/kg/d) was started three days after UUO induction and continued for 7 days. Plasma and kidney tissue were collected at the end of the experimental protocol. Results UUO mice demonstrated marked renal fibrosis with higher kidney hydroxyproline content and collagen positive area. Interventional DM509 treatment reduced hydroxyproline content by 41% and collagen positive area by 65%. Renal inflammation was evident in UUO mice with elevated MCP-1, CD45-positive immune cell positive infiltration, and profibrotic inflammatory gene expression. DM509 treatment reduced renal inflammation in UUO mice. Renal fibrosis in UUO was associated with epithelial-to-mesenchymal transition (EMT) and DM509 treatment reduced EMT. UUO mice also had tubular epithelial barrier injury with increased renal KIM-1, NGAL expression. DM509 reduced tubular injury markers by 25-50% and maintained tubular epithelial integrity in UUO mice. Vascular inflammation was evident in UUO mice with 9 to 20-fold higher ICAM and VCAM gene expression which was reduced by 40-50% with DM509 treatment. Peritubular vascular density was reduced by 35% in UUO mice and DM509 prevented vascular loss. Discussion Interventional treatment with DM509 reduced renal fibrosis and inflammation in UUO mice demonstrating that DM509 is a promising drug that combats renal epithelial and vascular pathological events associated with progression of CKD.